Toxicity of sodium and potassium ions on performance of UASB system - Seni Karnchanawong (2018)
The objective of this study was to investigate the toxicity of Na + and K + ions on performance of upflow anaerobic sludge blanket (UASB) system. Three laboratory-scale UASB reactors, 15.8 - l working volume, were employed with 1 reactor operated as control. They were loaded at organic loading rate (OLR) of 5 kg COD/(m 3 -d), treating synthetic wastewater with COD concentration ~ 5000 mg/l. Na + and K + ions were added in the range of 1010 - 7180 and 41 - 7320 mg/l, respectively. No toxicity was observed at influent Na + and K + concentrations up to 3340 and 2750 mg/l, respectively. Slight inhibitions on COD removal were founded at Na + and K + concentrations of 4610 and 3920 mg/l, respectively, but moderate effect on biogas production had occurred. When Na + and K + concentrations were increased to 7180 and 7320 mg/l, respectively, strong inhibitions were observed with COD removal dropped to 45.5 and 48.8%, respectively. Ratios of biogas productions, as compared to the control reactor, were dropped to 0.31 and 0.32, respectively. Increasing cation concentrations had more detrimental effect on biogas production than COD removal. © (2014) Trans Tech Publications, Switzerland.